MAKNA RITUAL NASI PUNJUANG DALAM AQIQAH ANAK DESA PULAU BUSUK JAYA KECAMATAN INUMAN KABUPATEN KUANTAN SINGINGI - Nurdianti, Tri; ", Yasir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Nasi Punjuang Ritual is one of the traditional traditional rituals originating from the village of Pulau Busuk Jaya, which is located in Inuman District, Kuantan Singingi Regency. This ritual is held to protect oneself from evil spirits when holding an aqiqah event for babies who will carry out one of their obligations as religious people. The purpose of this study was to determine the symbolic meaning in the Nasi Punjuang ritual. As for the sub-focus, namely the meaning of the situation, the product of interaction, and the interpretation of the Nasi Punjuang ritual tradition.This study uses a qualitative research method with a symbolic interaction approach. Informants in this study were determined purposively, consisting of two core implementers and three general public who had been selected with certain considerations. Data collection techniques in this study include observation, interviews, and documentation.The results of this study indicate that the symbols in the Nasi Punjuang ritual as a self-fences for the Pulau Busuk Jaya village include physical objects such as offerings of Nasi Punjuang and various equipment with special meanings in each part. While the social objects in the Nasi Punjuang ritual in children's aqiqah include the movements of the village elders, the meaning of mantras and prayers in the Nasi Punjuang ritual, the meaning of time behind the implementation of the ritual. The meaning of the product of social interaction includes the meaning of the head of the tribe who interprets it as the identity of the village community of Pulau Busuk Jaya, from the village elders interpreting it as a profitable ritual which is a legacy from previous ancestors, the meaning of the Baby's Parents or the Host who interprets as a protector to avoid danger and the meaning of the General Public interprets it as a form of respect for ancestors. The meaning of the interpretation of the Nasi Punjuang ritual in children's aqiqah includes closed actions related to motivation and feelings, while open actions are seen from happy facial expressions.